مقاربة أسلوبية في قصيدة ذكرى المولد لأحمد شوقي - تجاني, نعيمة; سعودي, سليمة; بوزيدي, الزهرة; جاب الله, وردة (University of Eloued جامعة الوادي, 2024)
سعى ىذا البحث إ عارء أحمد شوقي ّ لى دارسة تحليلية لقصيدة( ذكرى المولد )لأمير الش وكانت دارستيا مقاربة أسلوبية نظار ،ةّ وغرضيا المديح النبوي جاءت على شكل مولدي لاختلاف مستوياتيا: الصوتي والبلاغي والتركيبي. حيث بدأت ، جاءت ىذه الدارسة مكونة من مدخل وفصلين وخاتمة وتي بما ّ بالمستوى الص ، يمثلو من موسيقى داخلية تناولت الأصوات المجيورة والميموسة، الصائتة والصامتة ّ أما الموسيقى الخارجية فكانت ل لوزن و وي. وكان ّ القافية والر لا في الصور ّ المستوى البلاغي ممث البيانية؛ استعارة وتشبيو وكناية، إلى جانب البديع وما فيو من طباق وجناس وتصريع. بالإضافة إلى الجانب التركيبي وما فيو من أزمنة الفعل؛ ماض ومضارع و أمر. وقد استنتجنا في الأخير أن الشاعر استعمل البحر الوافر وزنا ليذه القصيدة، لوفرة حركاتو واستغارقو في تجارب كثيرة، وىو إشارة لوفرة الخير الذي يأتي من مدح الرسول صلى و الجانب البلاغي جاء ، الله عليو وسلم. كما جاءت القافية موحدة مطلقة روييا حرف الباء ثريا بالصور البيانية التقليدية وعلى أرسيا الاستعارة التي حافظت على يّ الطابع الحس والمادي التصويري، مع حضور الفعل الماضي بصفة مكثفة في القصيدة ليدل على استغارق الشاعر في أ ىذا ِ ص الزمن ىويتو وبيئتو. ُّ حداث مضت This research sought an analytical study of the poem (The Anniversary of the Birth) by the Prince of Poets, Ahmed Shawqi, and its purpose was to praise the Prophet, which came in the form of a Mawlid poem, and its study was as a stylistic approach due to its different levels: such as vocal, rhetorical, and synthetic. This study consisted of an introduction and two chapters. It began with the vocal level, as it represents internal music. It dealt with voiced and whispered sounds, voiced and silent, while external music was for meter, rhyme, and narration, and the rhetorical level was represented in graphic images. Metaphor, simile, and metonymy, in addition to the wonderful and its antithesis, alliteration, and collocation, then to the good and constructive meanings and style. We touched on the syntactic aspect of the verb tenses of the past, present, and imperative. In the end, we concluded that the poet used the abundant sea as weight for this poem, due to the abundance of his movements and his absorption in many experiences, which is an indication of the abundance of goodness that comes from praising the Messenger, may God bless him and grant him peace. The rhyme was unified, unified, and absolute, narrated by the letter b, and the rhetorical aspect was rich in traditional graphic images, most notably metaphor, which preserved the sensual, material, and pictorial character. The intense presence of the past tense in the poem is evidence of the poet’s absorption in past events and this time assuming his identity and environment.
أدب حيث ومعاصر